1989
DOI: 10.1002/actp.1989.010400401
|View full text |Cite
|
Sign up to set email alerts
|

Copolymerization of a multiallyl monomer with styrene

Abstract: The free-radical copolymerization of the multiallyl monomer poly(N-allylmethacrylamide) with styrene in diluted dioxane solutions was studied. The chain transfer constant of the polystyrene radical to the multiallyl monomer was determined. The effect of temperature, initiator concentration, and initial composition of the monomer mixture on the copolymerization yield was examined and the content of unreacted allyl bonds and molecular weight were determined. Based on I R spectroscopy, 'H NMR, and elemental analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…On the other hand, one of the most effective methods that could be applied to obtain copolymers with multiblock structure is template copolymerization. Several authors have done many works to explain the template copolymerization process. It was found that the template copolymer exhibited a longer sequence distribution of monomers than that of traditional copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, one of the most effective methods that could be applied to obtain copolymers with multiblock structure is template copolymerization. Several authors have done many works to explain the template copolymerization process. It was found that the template copolymer exhibited a longer sequence distribution of monomers than that of traditional copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…This paper continues the research described in recent publications on the deposition of polymercomplex layers onto various textile fabrics [7,8,12,13]. In order to understand how the type, composition and architecture of the deposited polymer layer influences the properties of the prepared materials, previously synthesized and well-characterized PEI-PEtOx and bPEI polymers [14][15] have been used for deposition on nonwoven polypropylene substrates.…”
Section: Introductionmentioning
confidence: 72%
“…This method makes it possible to obtain materials with the combined properties of both surface and layer. By the inclusion of appropriate layers, it is possible to fine tune the properties of the surfaces e.g their hydrophilicity [12], dyebility [7], surface resistance [7], thermal stability [8] and electrokinetic properties [13]. Variations in the surface acidic or basic strength depending on the properties of deposited layers were also observed with the aid of an appropriate dye [7].…”
Section: Introductionmentioning
confidence: 99%
“…anti‐static coatings for plastics, sensors, light‐emitting diodes, fuel cells, polymer capsules, etc.). Polyelectrolyte self‐assemblies of different textile fibres and structures were studied in general and these studies investigated only the possibility of using the electrostatic self‐assembly method for textile materials [3–6]. In our previous studies, we investigated the possibility of nanoparticle film deposition on cotton fabrics with electrostatic self‐assembly deposition, and we showed that the electrostatic self‐assembly process could be used to obtain functional textiles with antimicrobial, ultraviolet (UV)‐protective, self‐cleaning and flame‐retardant properties [7–9].…”
Section: Introductionmentioning
confidence: 99%